2002
DOI: 10.1029/2002ja009302
|View full text |Cite
|
Sign up to set email alerts
|

Global ULF disturbances during a stormtime substorm on 25 September 1998

Abstract: [1] Quasiperiodic perturbations of ionospheric plasma with $10 min occurrence periods were observed by incoherent scatter radars (ISR) in high-latitude and midlatitude ionosphere after the onset of a stormtime substorm. The latter occurred during a period of complex dynamical activity and had a number of unusual characteristics. The perturbations indicate ultralow frequency (ULF) electric field enhancements over the Northern Hemisphere. Specifically, strong subauroral electric fields are associated with the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 53 publications
(63 reference statements)
4
44
0
Order By: Relevance
“…This is good indirect evidence that Yakutsk was located in the auroral oval around 16 UT (01 LT). The most equatorward trough location around 16 UT is confirmed by the coherent echo observations (Mishin et al, 2002) with the Irkutsk ISR at the same time. …”
Section: Substorm On October 24 2003supporting
confidence: 82%
“…This is good indirect evidence that Yakutsk was located in the auroral oval around 16 UT (01 LT). The most equatorward trough location around 16 UT is confirmed by the coherent echo observations (Mishin et al, 2002) with the Irkutsk ISR at the same time. …”
Section: Substorm On October 24 2003supporting
confidence: 82%
“…ULF oscillations with a typical period of 10-15 min have been reported for polar boundary intensifications (PBIs) associated with BBFs (Lyons et al, 2002) and during substorms simultaneously in the magnetotail, at geosynchronous orbits and on ground (Sánchez et al, 1997;Mishin et al, 2002). While some claim that these oscillations are field line resonances with frequencies compatible with global cavity modes associated with substorm activity (Samson et al, 1992;Sánchez et al, 1997), others have suggested that they are externally driven by solar wind pressure (Kepko and Spence, 2003) and/or IMF changes (Mishin et al, 2002). Figure 13 displays the power frequency spectra of the solar wind pressure, the duskward electric field measured by Geotail and the reconnection electric field from the ESR data.…”
Section: Discussionmentioning
confidence: 99%
“…SAID are considered as a subset of the subauroral polarization streams (SAPS) that include plasma flow events both broad and narrow extents in latitude (Foster and Burke, 2002). Sometimes, SAPS are highly variable and structured (Maynard et al, 1980;Erickson et al, 2002;Mishin et al, 2002Mishin et al, , 2003aMishin et al, , 2004Foster et al, 2004;Mishin and Burke, 2005). Especially strong SAPS-wave structures (SAPSWS), in which V W -oscillations reach AE1-2 km/s and exceed the dc component, follow stormtime substorm onsets.…”
Section: Introductionmentioning
confidence: 99%